A Junior High School English Teacher’s Experience in Motivating EFL Learners: A Narrative Study - Bima Ichi Anugerah (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Motivation plays a crucial role in learning, as it drives learners to perform better and achieve their goals. It can develop passion and enthusiasm, making it essential for EFL learners to understand the importance of motivation in learning English language. A lack of motivation can be an obstacle for learners, making it crucial for both learners and teachers to understand the importance of motivation in learning. Teachers should remind their learners of the importance of English language for their education and future, thereby keeping them motivated throughout the learning process. Nunan (2010) highlights the challenges faced by some learners in their social and psychological development, such as managing needs, maintaining attention, and lack of motivation. To overcome these issues, teachers should provide varied learning activities, interesting methods, and a comfortable environment, while also emphasizing the importance of the English language. This study used a narrative research design to explore the junior high school English teacher’s experiences regarding the strategies and hindrances in motivating EFL learners. I conducted this study at the islamic junior high school in Banyuwangi. I collected the data by conducting two interviews with my participant. The participant was a female English teacher who has been teaching English for thirteen years. She has friendly personality that a lot of her students, including myself, have a good relationship with her. I analyzed the data by using thematic analysis by Braun and Clarke (2006). The analysis revealed two themes: (1) motivational strategies applied by the teacher, (2) hindering factors in motivating the learners. I identified these themes from the codes that I generated from the interview transcribes. The findings revealed two themes; Motivational Strategies Applied by the Teacher and Hindering Factors in Motivating the Learners. The first theme was broken down into four subthemes. They are building a good relationship, using interesting learning methods, using various media, and maintaining learners’ motivation. The second theme was broken down into seven subthemes. The first four subthemes are learners’ background, low interest, inattention, and shiftlessness which came from the learners themselves. And then the last three subthemes are inappropriate classroom setting, unsupportive peer behavior, and time constraints which arose from the learners’ surroundings. Not forget to mention that this research aims to explore and investigate the junior high school English teacher’s experiences regarding the strategies and hindrances in motivating EFL learners, and based on the findings, the English teacher at the Islamic Junior High School in Banyuwangi applied several strategies to keep the learners motivated throughout the learning process. However, she also faced several hindrances in motivating them. Lastly, I would like to provide several suggestions regarding my experience in doing this research. The first suggestion is for the English teachers. English teachers should stay updated with modern technology developments to facilitate an engaging teaching-learning process. Utilizing technology such as computers, smartphones, interactive websites, apps, and videos will keep students interested and motivated throughout the lesson. The second suggestion is for the researchers. It would be preferable for other researchers to look into this subject using a different research design and data analysis technique if they would like to investigate the strategies and hindrances in motivating junior high school EFL learners.
Reuploud file repositori 4 Feb 2026_Firli
Keywords: Learning English; Motivating EFL Learners; Narrative Study; The Role of Learners